A marine cement and its use in corrosion resistance

CN118771760BActive Publication Date: 2026-10-09BEIJING UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410839781.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2026-10-09
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

[0003]但由于不同地域的海洋环境有所差异,且不同的海上工程应用目标不同,导致在海工水泥的研发过程中往往很难寻求抗蚀性和耐久性的平衡

Benefits of technology

[0034] The marine cement provided by this invention and its application in corrosion resistance improve the corrosion resistance of marine cement by adjusting the sulfur-aluminum ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771760B_ABST
    Figure CN118771760B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of special cement materials, in particular to a marine cement and application thereof in corrosion resistance. The sulfur-aluminum ratio of the marine cement is controlled to be 0.29-0.33 or 0.37-0.39. The marine cement and the application thereof in corrosion resistance provided by the application improve the corrosion resistance of the marine cement by regulating the sulfur-aluminum ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special cement materials technology, and in particular to a marine cement and its application in corrosion resistance. Background Technology

[0002] During marine development, marine engineering projects face severe seawater corrosion problems. Therefore, researchers have conducted extensive research in the field of "corrosion-resistant cement-based materials." Compared with ordinary silicate cement, the most important characteristic of marine cement is that marine engineering structures made from marine cement have strong corrosion resistance and can adapt to complex and harsh marine environments.

[0003] However, due to the differences in marine environments across different regions and the varying objectives of different offshore engineering applications, it is often difficult to strike a balance between corrosion resistance and durability during the research and development of marine cement. Furthermore, there are currently no definitive guidelines for controlling corrosion resistance using various admixtures.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a marine cement and its application in corrosion resistance, improving the resistance of marine cement to sulfate and chloride ion corrosion, and meeting the needs of various marine engineering projects for resistance to sulfate and chloride ion corrosion.

[0006] This invention provides a marine cement in which the sulfur-aluminum ratio of all its admixtures is controlled to be 0.29-0.33 or 0.37-0.39.

[0007] This invention discovers that by controlling the sulfur-aluminum ratio of marine cement to the above-mentioned range, the corrosion resistance of marine cement can be significantly improved, especially its resistance to sulfate and chloride ion erosion, thereby enhancing its durability and improving its practical application capability.

[0008] In this invention, the sulfur-aluminum ratio is calculated as the ratio of the mass content of SO3 to the mass content of Al2O3 in all admixtures.

[0009] In order to adjust the sulfur-aluminum ratio of marine cement to the above-mentioned range, the present invention optimizes and adjusts the admixtures.

[0010] Preferably, the marine cement includes the following admixtures: clinker, mineral powder and fly ash.

[0011] More preferably, the clinker includes cement clinker and gypsum dihydrate.

[0012] More preferably, the mineral powder includes S95 grade slag powder and / or S75 grade slag powder; even more preferably, the mineral powder includes S95 grade slag powder.

[0013] More preferably, the fly ash includes Class I fly ash and / or Class II fly ash; even more preferably, the fly ash includes Class I fly ash.

[0014] This invention uses the design value of the sulfur-aluminum ratio as a reference index. From the perspective of reducing excessive heat release during cement hydration and saving cement clinker in marine engineering construction, it uses high-specific-surface-area S95 grade slag powder as a large proportion of admixture. During hydration, the amount of ettringite formed is altered by adjusting the sulfur-aluminum ratio, further affecting the formation of AFm. This improves the density of marine cement, thereby enhancing its related performance. The formation of ettringite provides more growth and attachment sites for CSH gel, acting as a "skeleton." Simultaneously, the slag powder can react with the hydration product Ca(OH)2 of tetracalcium aluminoferrite to generate more CSH gel, enhancing the internal adhesion of the cement base and further improving density to a certain extent. Secondly, the slag powder can effectively reduce the heat of hydration of marine cement, preventing a series of problems such as decreased durability caused by overheating.

[0015] Meanwhile, the admixtures such as Grade I and Grade II fly ash primarily exhibit a spherical particle shape. This spherical shape positively impacts the reduction of water consumption during cement mixing and the workability of the mixed cement. Specifically, this invention uses Grade I fly ash, which boasts superior performance compared to other grades, exhibiting a strong ball-bearing effect that reduces the poor workability of cement caused by silica fume and other contaminants during use.

[0016] In this invention, by adjusting the amount of admixtures such as clinker, slag powder, and fly ash, and by affecting the formation of ettringite through changes in the sulfur-aluminum ratio, the corrosion resistance and various performance characteristics of cement used in marine engineering in different regions can be balanced.

[0017] Preferably, the mass ratio of cement clinker to dihydrate gypsum is 2.75 to 5.25:1.

[0018] Preferably, the specific surface area of ​​the dihydrate gypsum is 360–380 cm². 2 / g, the specific surface area of ​​the cement clinker is 330-350cm². 2 / g; and / or, the specific surface area of ​​the mineral powder is 4000-5000 cm². 2 / g; and / or, the specific surface area of ​​the fly ash is 4500–6000 cm². 2 / g.

[0019] Preferably, the method for preparing the dihydrate gypsum includes: crushing natural gypsum minerals into fragments of 30-40 mm, and then mixing the crushed dihydrate gypsum fragments with isopropanol and ball milling them; more preferably, the ball milling time is 10-30 min; more preferably, the amount of isopropanol used is 1-3% of the mass of the dihydrate gypsum fragments.

[0020] As a preferred embodiment, the preparation method of the dihydrate gypsum includes: 1. First, adding natural gypsum mineral raw materials to a jaw crusher in batches, with a maximum of 2 kg added each time. After the jaw crusher finishes working, the minerals are crushed into pieces of 30-40 mm and then removed for use; 2. Adding the crushed dihydrate gypsum pieces to a vertical ball mill in batches, with 7-8 kg added each time, and adding isopropanol at a rate of 1-3% of the mass of the dihydrate gypsum added each time. The ball milling time is controlled within 20 minutes.

[0021] In this invention, by adding the above-mentioned amount of isopropanol to the preparation method of gypsum dihydrate, it is possible to effectively prevent the deterioration caused by the loss of bound water due to overheating of minerals during the heating process, and reduce the adhesion between gypsum dihydrate and the grinding blocks in the ball mill.

[0022] Preferably, the residue on the 45μm sieve of the admixture is controlled to be 6% to 20%.

[0023] Preferably, the marine cement comprises the following admixtures in parts by weight: 25-55 parts clinker, 38-64 parts mineral powder, and 4-10 parts fly ash.

[0024] Preferably, when the clinker comprises 25 parts by weight but less than 35 parts, the mineral powder comprises 58 to 64 parts and the fly ash comprises 4 to 10 parts; when the clinker comprises 35 to 45 parts, the mineral powder comprises 45 to 55 parts and the fly ash comprises 4 to 10 parts; when the clinker comprises 45 parts by weight but less than or equal to 55 parts, the mineral powder comprises 38 to 48 parts and the fly ash comprises 4 to 10 parts.

[0025] Preferably, the admixture also includes one or more of silica fume, metakaolin, limestone powder, steel slag powder, hydrotalcite, and bauxite.

[0026] In this invention, the addition of admixtures such as silica fume changes the sulfur-aluminum ratio in the raw materials and increases the density through different physical and chemical methods, thereby further improving the resistance of marine cement to seawater corrosion.

[0027] More preferably, the admixture also includes silica fume.

[0028] In this invention, silica fume admixtures play three main roles in the preparation and use of marine cement: 1. The high activity of SiO2 in silica fume provides excellent lubrication and grouting effects, filling pores and microcracks in cement mortar, thereby improving the density and compactness of the cement mortar. 2. The highly active SiO2 accelerates cement hydration, improving the compressive and flexural strength at various stages of cement hardening. 3. The hydrated calcium silicate in silica fume can combine with various trace elements in cement minerals to form chemically stable substances, thus stabilizing the various products after cement hydration and improving the chemical stability and corrosion resistance of cement mortar.

[0029] More preferably, the specific surface area of ​​the silica fume is 20-25 m². 2 / g.

[0030] Secondly, the present invention further provides a method for preparing the marine cement, comprising: mixing clinker, mineral powder and fly ash to obtain marine cement.

[0031] Preferably, the preparation method of the marine cement includes: mixing cement clinker with dihydrate gypsum and then ball milling to obtain mixed clinker; and then mixing the above mixed clinker with S95 grade slag powder, grade I fly ash and silica fume to obtain marine cement.

[0032] Thirdly, the present invention further provides the application of the aforementioned marine cement in corrosion resistance.

[0033] Preferably, the corrosion resistance includes resistance to sulfate ion and / or chloride ion corrosion.

[0034] The marine cement provided by this invention and its application in corrosion resistance improve the corrosion resistance of marine cement by adjusting the sulfur-aluminum ratio. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0036] Figure 1 These are the test results of marine cement samples prepared according to the embodiments and comparative examples provided by the present invention. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0038] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.

[0039] The mineral composition of the cement clinker used in the following embodiments is shown in Table 1: Table 1

[0040] The preparation method of the dihydrate gypsum includes: 1. Adding natural gypsum mineral raw materials to a jaw crusher in batches, with a maximum of 2 kg added each time. After the jaw crusher finishes working, the minerals are crushed into pieces of 30-40 mm and then taken out for use; 2. Adding the crushed dihydrate gypsum pieces to a vertical ball mill in batches, with 7-8 kg added each time, and adding isopropanol at 1-3% of the mass of the dihydrate gypsum added at that time. The ball milling time is controlled within 20 minutes.

[0041] The specific surface area of ​​dihydrate gypsum is 360–380 m². 2 / g; of which SO3 content is 53.95% and Al2O3 content is 0.63%.

[0042] The specific surface area of ​​S95 grade slag powder is 4000-5000 cm². 2 / g; of which Al2O3 content is 17.56%.

[0043] The specific surface area of ​​Class I fly ash is 4500–6000 cm². 2 / g; of which SO3 content is 2.05% and Al2O3 content is 31.34%.

[0044] The specific surface area of ​​silica fume is 18,000–20,000 cm². 2 / g; of which SO3 content is 0.45% and Al2O3 content is 1.67%.

[0045] The residue of the above-mentioned admixture on a 45μm sieve is 6% to 20%.

[0046] Example 1

[0047] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.39. The raw materials are weighed according to the following weight ratio: 50% mixed clinker, 38% S95 grade mineral powder, 10% grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 5.25:1. The raw materials are then homogenized, and the sample in Example 1 is designated as S1.

[0048] The samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0049] Example 2

[0050] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.38. The raw materials are weighed according to the following weight ratio: 50% mixed clinker, 40% S95 grade mineral powder, 8% grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 5.25:1. The raw materials are then homogenized, and the sample in Example 2 is designated as S2.

[0051] Samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Erosion" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Erosion".

[0052] Example 3

[0053] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.37. The raw materials are weighed according to the following weight ratio: 50% mixed clinker, 44% S95 grade mineral powder, 4% Grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 5.25:1. The raw materials are homogenized, and the sample in Example 3 is designated as S3.

[0054] The samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0055] Example 4

[0056] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.31. The raw materials are weighed according to the following weight ratio: 30% mixed clinker, 58% S95 grade mineral powder, 10% grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 2.75:1. The raw materials are homogenized, and the sample in Example 4 is designated as S4.

[0057] The samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0058] Example 5

[0059] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.32. The raw materials are weighed according to the following weight ratio: 30% mixed clinker, 60% S95 grade mineral powder, 8% grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 2.75:1. The raw materials are homogenized, and the sample in Example 5 is designated as S5.

[0060] The samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0061] Example 6

[0062] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.33. The raw materials are weighed according to the following weight ratio: 30% mixed clinker, 64% S95 grade mineral powder, 4% grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 2.75:1. The raw materials are homogenized, and the sample in Example 6 is designated as S6.

[0063] The samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0064] Example 7

[0065] This embodiment provides a marine cement with an SO3 / Al2O3 ratio of 0.29. The raw materials are weighed according to the following weight ratio: 40% mixed clinker, 45% S95 grade mineral powder, 10% grade I fly ash, 3% silica fume, and 2% metakaolin. The mixed clinker is a mixture of cement clinker and dihydrate gypsum in a mass ratio of 4:1. The raw materials are homogenized, and the sample in Example 7 is designated as S7.

[0066] The samples were prepared and cured according to the different molding requirements in GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0067] Example 8

[0068] This embodiment provides a marine cement, which differs from Embodiment 7 in that: dihydrate gypsum is replaced with an equal amount of commercially available desulfurized gypsum. The desulfurized gypsum is purchased from Shandong Shunxing Cement Co., Ltd., and has the following composition: SO3 content 52.02%, CaO content 36.68%, SiO2 content 5.05%, Al2O3 content 2.18%, MgO content 1.67%, and a specific surface area of ​​350 cm². 2 / g. The sample from Example 8 is designated as S8.

[0069] The sample preparation and curing were carried out in accordance with the molding requirements of GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0070] Comparative Example 1

[0071] This comparative example provides a marine cement with an SO3 / Al2O3 ratio of 0.35. The raw materials are weighed according to the following weight ratio: 35% mixed clinker, 55% S95 grade mineral powder, 8% grade I fly ash, and 2% silica fume. The mixed clinker is a mixture of cement clinker and dihydrate gypsum with a mass ratio of 3.375:1. The raw materials are homogenized, and the sample in Comparative Example 1 is designated as S9.

[0072] The sample preparation and curing were carried out in accordance with the molding requirements of GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Attack" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Attack".

[0073] Test case

[0074] The data obtained by testing different samples of Examples S1 to S9 above according to GBT42272-2022 "Test Method for Chloride Ion Diffusion Coefficient of Cement Mortar", GBT749-2008 "Test Scheme for Cement Resistance to Sulfate Erosion" and GBT38140-2019 "Test Method for Cement Resistance to Seawater Erosion" are shown in Table 2.

[0075] Table 2

[0076] Marine cement samples prepared according to the mix proportions shown in the examples and comparative examples were tested for compressive strength at 3d, 28d, and 90d in accordance with GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are as follows: Figure 1 As shown.

[0077] The above embodiments illustrate that when the SO3 / Al2O3 ratio is between 0.29 and 0.33, or between 0.37 and 0.39, marine cement exhibits excellent corrosion resistance, meeting the requirements of marine engineering for corrosion resistance. Due to the large addition of mineral powder and fly ash, the pozzolanic effect is strong, effectively reducing the heat of hydration and allowing the marine cement proposed in this invention to maintain significant strength improvement in the later stages. In summary, the novel corrosion-resistant adjustable marine cement designed based on the sulfur-aluminum ratio of this invention not only has high resistance to sulfate attack but also high resistance to chloride and seawater attack. It allows for reasonable adjustment of durability and corrosion resistance in marine engineering projects in different sea areas according to actual conditions, achieving optimal adaptability.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A type of marine cement, characterized in that, The sulfur-aluminum ratio of all its admixtures is controlled to be 0.29~0.33 or 0.37~0.39; The admixture comprises the following components: 25-55 parts clinker, 38-64 parts mineral powder, and 4-10 parts fly ash; the clinker includes cement clinker and dihydrate gypsum; the mineral powder includes S95 grade slag powder and / or S75 grade slag powder; the fly ash includes Grade I fly ash and / or Grade II fly ash.

2. The marine cement according to claim 1, characterized in that, The mass ratio of cement clinker to dihydrate gypsum is 2.75~5.25:

1.

3. The marine cement according to claim 1, characterized in that, The specific surface area of ​​the dihydrate gypsum is 360~380 cm². 2 / g, the specific surface area of ​​the cement clinker is 330~350cm². 2 / g; and / or, the specific surface area of ​​the mineral powder is 4000~5000 cm². 2 / g; and / or, the specific surface area of ​​the fly ash is 4500~6000 cm². 2 / g.

4. The marine cement according to claim 3, characterized in that, The preparation method of the dihydrate gypsum includes: crushing natural gypsum minerals into 30-40mm fragments, and then mixing the crushed dihydrate gypsum fragments with isopropanol and ball milling them.

5. The marine cement according to claim 4, characterized in that, The ball milling time is 10-30 min; the amount of isopropanol used is 1-3% of the mass of the gypsum dihydrate fragments.

6. The marine cement according to claim 1, characterized in that, The residue on the 45μm sieve of the admixture is controlled to be 6%~20%.

7. The marine cement according to claim 1, characterized in that, When the clinker comprises 25 parts by weight but less than 35 parts by weight, the mineral powder comprises 58 to 64 parts by weight and the fly ash comprises 4 to 10 parts by weight; when the clinker comprises 35 to 45 parts by weight, the mineral powder comprises 45 to 55 parts by weight and the fly ash comprises 4 to 10 parts by weight; when the clinker comprises 45 parts by weight but less than or equal to 55 parts by weight, the mineral powder comprises 38 to 48 parts by weight and the fly ash comprises 4 to 10 parts by weight.

8. The marine cement according to any one of claims 2 to 7, characterized in that, The admixture also includes one or more of the following: silica fume, metakaolin, limestone powder, steel slag powder, hydrotalcite, and bauxite.

9. The marine cement according to claim 8, characterized in that, The specific surface area of ​​the silica fume is 20~25m². 2 / g.

10. The application of the marine cement according to any one of claims 1 to 9 in corrosion resistance.

Citation Information

Patent Citations

  • Maritime concrete cement

    CN101659535A

  • High-corrosion-resistance maritime work cementing material as well as preparation method and application thereof

    CN111704419A